Onomastic code in Mandelstam’s poetry - Kihney, Liubov (Literatūra, 2019)
The article explores the principles of anagraming and intertextual cryptography in the work of Osip Mandelstam related to his own name and surname. It is proved that onomastic ciphers dissolved in poetic fabric (embodied in the images of Hagia Sophia, Joseph, the staff, axis, wasp, Hosian, etc.) add up to the author’s myth about the World Tree / World Axis, which, through a system of complex intertextual references, draws into themselves a number of mythological paradigms of world culture. At the same time, the uniqueness of the myth created by Mandelstam lies in the fact that within the author’s system of onomastic correspondences, all images are likened to each other, and their semantic fields become interpenetrable and mobile, which is explained by their ascent to the single sound-semantic code of the poet’s name and surname.